Endodontic Buildups - A Case Series - Rao, Sheetal; Ballal, Nidambur Vasudev (The Journal of Dentists, 2017)
Disinfection of the root canal space is one of the main principles of endodontic therapy. Very often the teeth that need root canal therapy are also those that have lost a substantial amount of tooth structure. Hence, placement of rubber dam for isolation becomes difficult if not impossible. Improper isolation is one of the important reasons for a compromised root canal therapy. Having an access cavity that is four walled goes a long way in helping the goals to succeed. This case series gives an over view of the commonly used techniques for pre-endodontic tooth build up to enhance the isolation during endodontic treatment.